Peran Pengendalian Internal dalam Optimalisasi Pengelolaan Persediaan pada Perusahaan Distribusi dan Perdagangan - Septiawan, Hendra Sutarto; Vendy, Vicky (Journal of Trends Economics and Accounting Research, 2025)
This study aims to analyze the role of internal control systems in optimizing merchandise inventory management within distribution and trading companies in Surabaya. Adopting a qualitative approach with a case study method, data was collected through interviews, observations, and documentation. The findings indicate that the implementation of an internal control system, based on the COSO framework, is well-established, along with the utilization of systems and procedures related to the inventory accounting system. The organizational structure is clearly defined, with duties and authorities aligned with Standard Operating Procedures (SOPs), ensuring effective inventory oversight. The company employs two inventory management methods: FIFO for consumer products and FEFO for pharmaceutical and medical device products. Both methods effectively manage expiry risks and maintain stable product supply. The company utilizes DTMS technology and manual recording for inventory tracking, automatically managing company transaction data. Regular supervision by external bodies such as BPOM, BPK, SPI, and KAP helps prevent fraud risks within the company. While the internal control system operates effectively, employee negligence remains a factor influencing company operations.